Understanding the Nature of Ethnic Entrepreneurship: A Systematic Literature Review - Salehi, Ali (Journal of Ethnic and Cultural Studies, 2026)
Ethnic entrepreneurship has attracted growing scholarly attention, yet its conceptual boundaries and practical implications remain ambiguous. This study enhances understanding of the phenomenon by conducting a systematic literature review that synthesizes insights from authoritative and peer-reviewed sources. The analysis identifies clear indicators distinguishing ethnic entrepreneurship from non-ethnic forms, including definitional boundaries, the unique characteristics of ethnic entrepreneurs, and the interplay of economic, social, and cultural motivations. The findings reveal that while ethnic entrepreneurs face common challenges such as high failure rates, resource constraints, and integration barriers, they also rely on distinctive strategies shaped by migration experiences and co-ethnic networks. These include forming co-ethnic partnerships, pursuing franchising, relocating businesses, shifting sectors, and, in some cases, return migration. Success is further influenced by adaptation strategies, transnational ties, and community-based resources. The study contributes theoretically by positioning ethnic entrepreneurship as a distinct but related field within entrepreneurship research, demonstrating that entrepreneurial behavior is shaped not only by economic rationality but also by socio-cultural embeddedness. Practically, it provides insights for policymakers and support organizations to design targeted interventions that extend beyond purely economic measures and better reflect the lived realities of ethnic entrepreneurs. A conceptual framework is developed to integrate these findings, offering a foundation for future research and policy innovation.